GOVERNING REDD A Prerequisite Analysis for a Potential REDD Implementation in Kabupaten Maluku Tengah - , EMILIANUS YAKOB SESE TOLO, S. FIL, Dr. Erwan Agus Purwanto, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Nowadays, one of the global challenges is climate change caused by the enhancement of the global temperature. The increasing of global temperature is caused by two factors, namely industrial activities since industry revolution and the current global deforestation. Both have engendered the emission of GHGs to the atmosphere. The emission of GHG, finally, leads to the enhancement of the global temperature. The cheapest way to mitigate the impact of the enhancement of the global temperature is by preventing global deforestation. To create the fairness for the tropical forest countries, the developed countries establish a global strategy which is so-called REDD. By REDD, tropical forest countries will get the financial compensation if the could meet the emission reduction on the certain level. REDD projects have been implemented in some places in the world including Indonesia, for instance, in Central Kalimantan. However, REDD potency in Indonesia is not only in Kalimantan, but also in other places like Seram Island especially in the Maluku Tengah district. REDD potencies in the district are that the district has wide forest, Manusela National park and the history of deforestation. For understanding those REDD potencies in the Maluku Tengah district, the researcher did a scrutinized research. The researcher utilized qualitative research methodology by using qualitative data form the literature study, observation and in-depth interview. Those data were analyzed by the researcher to understand the research problem. The inference is that the Maluku Tengah district has huge potency for REDD implementation. However, before implementing REDD, all the problems regarding unclear forest border, low level of localsâ involvement and illegal logging have to be solved beforehand. Besides, REDD implementation in the Maluku Tengah district has to be based on the forest governance principles which respect for multi-stakeholder participation and decentralization of power among the engaged stakeholders. By doing so, the REDD implementation will bear fruit by meeting the emission reduction and poverty alleviation within the Maluku Tengah district.